Hybrid epoxy-silane coatings for improved corrosion protection of Mg alloy - Brusciotti, Fabiola
New hybrid epoxy-silane coatings, with added functionalities for improved performance and durability, were designed to increase the corrosion protection of magnesium alloys. The corrosion behavior of the coated AZ31 was studied through electrochemical impedance spectroscopy (EIS) in 0.05 M NaCl. The morphology and surface chemistry of the samples were also investigated through scanning electron microscopy (SEM) and Fourier transform infrared spectroscopy (FT-IR) before and after immersion in the electrolyte. The new hybrid silane coatings showed a high resistance to corrosion that persisted throughout one-month immersion in a pH-neutral NaCl solution. (c) 2012 Elsevier Ltd. All rights reserved.